O gênero em questão: crítica e formação nos Bildungsromane The Secret Life of Bees, de Sue Monk Kidd, e Sapato de salto, de Lygia Bojunga - Chatagnier, Juliane Camila [UNESP] (2014)
The aim of this work is to discuss concepts about gender, present in some theories and specific criticisms, and analyze two contemporary novels: the American - The Secret Life of Bees (2002), by Sue Monk Kidd, and the Brazilian - Sapato de salto (2006), by Lygia Bojunga. It is intended to collate the way each writer presents the protagonists’ formation process and to check how the form of the novel influences on the gender construction of the main characters in both works, once these novels are considered feminine Bildungsromane. It is pertinent to emphasize that the protagonists’ formation will be evaluated according to the adopted critical perspectives in which the subject is performative and claims positions as a mark of identity. Whereas the works are embedded in contemporary times, it attempts to show that women do not assume an inferior position to men anymore. A misogynistic and sexist tradition is broken in the novels, as Butler proposes, at the moment the authors give the weaker sex their turn and voice, thus introducing a discourse of rupture. As critical- theoretical apparatus, the prospects of Beauvoir (1974), Wittig (1982), Hollanda (1994) and Butler (1990, 2001, 2004) will be used about gender issues; Pinto (1990), Maas (2000) and Scwhantes (2007) works will be the basis for the study of traditional and female Bildungsromane, and the works by Laclau (1990), Ortiz (1994) and Santos (2001) will contextualize the contemporaneity